Students’ Perception of Higher Education Service Quality: An Empirical Study - Gupta, Manish (Indian Journal of Marketing, 2016)
Purpose: This paper investigated the service quality perceptions of students towards higher education services using the three component model of service quality proposed by Rust and Oliver (1994). It also attempted to diagnose the perceived service quality across various interfaces such as services provided by the placement cell, library, computer labs, faculty/school offices, proctor office, hostel, sports and health centre of an Institution. Design/Methodology/Approach: The present study is a descriptive study, respondents were selected randomly, and data was collected through a 22-item likert-type structured questionnaire from 250 students. Data was analyzed and interpreted with the help of SPSS software. Hypotheses framed for the research work were tested with the help of t-test, chi square, F-test to measure the variance and to accept or reject the hypotheses. Findings: The research results revealed how students assessed service quality. The study also revealed that there is a significant difference in service quality perceptions across various demographic variables; furthermore, the study provided insights into the service quality dimensions that have the greatest influence on student satisfaction and student loyalty. Practical Implications: The managements of HEIs could use the results of the research to improve the study processes and to increase the students’ satisfaction and loyalty. Originality/Value: The study presented a student-centered perceived service quality valuation and subsequent linkage of the evaluations to student loyalty.